Corrosion resistance of 2024 aluminum alloy coated with plasma deposited a-C:H:Si:O films - Tavares Mascagni, Daniela Branco [UNESP]; Pires de Souza, Maria Eliziane [UNESP]; Alvarenga Freire, Celia Marina de; Silva, Selma Luiza; Cipriano Rangel, Rita de Cassia [UNESP]; Cruz, Nilson Cristino da [UNESP]; Rangel, Elidiane Cipriano [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2014)
AA 2024 aluminum alloy is widely employed in aeronautic and automobilist industries. Its hardness and low density are attractive properties for such industrial areas. However, since it contains copper, it undergoes severe corrosion in aggressive media as saline or low Earth orbit environments. In this work, it was investigated the properties of films deposited by PECVD on AA 2024 aluminum alloy as well as the corrosion resistance of the film/substrate systems under different corrosive atmospheres. Films were prepared in a plasma atmosphere composed of 50% of oxygen and 50% of hexamethyldisiloxane resulting in a total gas pressure of 4.0 Pa. Plasma ignition was promoted by the application of radiofrequency signal (13.56 MHz) to the sample holder while grounding the topmost electrode. The plasma excitation power, P, was changed from 10 to 80 W in the six different set of experiments. Film thickness, measured by profilometer, increases by 5 times as P was elevated from 10 to 80 W. As demonstrated by the infrared spectra of the samples, films are essentially organosilicons with preservation of functional groups of the precursor molecule and with creation of different ones. The oxide proportion and the structure crosslinking degree are affected by the plasma excitation power. According to the results obtained by sessile drop technique, hydrophilic to moderately hydrophobic films are produced with changing P from 10 to 80 W. The corrosion resistance, evaluated by salt spray and electrochemical impedance spectroscopy, EIS, experiments, in general increases after film deposition. It is demonstrated that film deposition improves, in up to 36 times, the resistance of the alloy to salt spray attack. It is also shown an improvement of about 240 times in the alloy resistance under NaCl solution by the EIS data. Micrographs acquired by Scanning Electron Microscopy after the corrosion tests furnish further information on the importance of the layer physical stability on its barrier properties. Furthermore, films highly protect the alloy against the oxygen attack. Interpretations are proposed based on the modification of the plasma kinetics with P, altering film structure, composition and properties.
Keywords: PECVD; Plasma treatment; Corrosion protection; 2024 aluminum alloy